How is the last Argentine dictatorship taught to young people? School practices of the recent past in the city of La Plata (Clepsidra - Interdisciplinary Journal of Memory Studies, 2021)
The dispute over the interpretation and use in the present of the historical events that occurred more than 40 years ago, after the last coup in Argentina, has been one of the axes through which our democratic life has traveled and continues. High school as a space for the construction of collective memory has not been alien to these transmission processes of the recent past, which is part of the latest educational reforms and is present as content in the curricular designs of the subject History of fifth and sixth year of the secondary level of the Province of Buenos Aires. This article analyzes the complex fabric of teaching and learning practices of the recent Argentine past in sixth-year history classes at a secondary school in the city of La Plata after these curricular reforms.
Keywords: school practices, recent past, memory, teaching history